The Extended Likeability Framework: A Theoretical Framework for and a Practical Case of Designing Likeable Media Applications for Preschoolers. (5th November 2008) - vanden Abeele, Vero; Zaman, Bieke
Abstract : A theoretical framework and practical case for designing likeable interactive media applications for preschoolers in the home environment are introduced. First, we elaborate on the theoretical framework. We introduce the uses and gratifications paradigm (U&G). We argue that U&G is a good approach to researching likeability of media applications. Next, we complete the U&G framework with expectancy-value (EV) theory. EV theory helps us move from theoretical insights to concrete design guidelines. Together, the U&G framework and the EV model form the foundation of our extended likeability framework for the design and evaluation of interactive media applications, for preschoolers in the home environment. Finally, we demonstrate a practical case of our extended likeability framework via the research project CuTI. The CuTI project aims at revealing those particular user gratifications and design attributes that are important to support playful behaviour and fun activities of preschoolers in the home environment.